Synthesis of New Reagents and Studying of (Spectral, Chromatography, Thermal, Solubility) Behavior - Nagham Mahmood Aljamali (Journal of Global Pharma Technology, 2017)
New reagents were prepared from cephalexine drug as macro reagents via several steps like ( esterification , substitution , condensation, insertion ) reactions to produce new analytical reagents . The first reagent involved two imine group , while the second reagent included two amide groups ,and third reagent involved two amide as a cycle by insertion reaction. Our reagents investigated by chemical techniques like ( FT.IR , H.NMR , Mass )- Spectra and studied through ( chromatographic curves , thermo curves ) ., which indicated our results and gave evidences for formatted reagents. Keywords: Reagent, Ester, Amide, Insertion, Cephalexine.